Danish translation, cross-cultural adaptation, and electronic migration of the World Endometriosis Research Foundation Endometriosis Phenome and Biobanking Harmonisation Project Endometriosis Patient Questionnaire - Thomsen, Line Holdgaard; Vexø, Laura Emilie; Schnack, Tine Henrichsen; Hansen, Karina Ejgaard; Forman, Axel; Hartwell, Dorthe; Nielsen, Henriette Svarre; Hummelshoj, Lone; Nyegaard, Mette; Madsen, Mette Elkjær (Frontiers in Global Women's Health, 2023)
Objectives This study aims to translate and cross-culturally adapt the standard version of the World Endometriosis Research Foundation (WERF) EPHect Endometriosis Patient Questionnaire (EPQ) into Danish and to ensure equivalence of a Danish electronic version. Methods The translation, cultural adaption, and electronic migration followed recommendations from the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) and the Critical Path Institute. Ten women with endometriosis were enrolled for cognitive debriefing of the paper version (pEPQ) after translation and back translation. The questionnaire was then migrated into an electronic version (eEPQ) and subsequently tested for usability and measurement equivalence by five women with endometriosis. Results Cross-cultural alterations were needed for medical terms, response options for ethnicity, the educational system, and measurement units. Thirteen questions were altered after back translation, while 21 underwent minor changes after cognitive debriefing. After testing the eEPQ, 13 questions were altered. Questions tested for measurement equivalence across the two modes of administration were found comparable. The median time-to-complete the pEPQ and eEPQ was 62 min (range: 29–110) and 63 min (range: 31–88), respectively. General comments included the questionnaire being relevant but long and repetitive. Conclusions We find the the Danish pEPQ and eEPQ similar and comparable to the original English instrument. However, attention must be drawn to questions regarding measurement units, ethnicity, and educational systems before cross-country comparison. The Danish pEPQ and eEPQ are suitable for obtaining subjective data on women with endometriosis.